2016
DOI: 10.1111/vru.12350
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anatomical Variation of the Sixth Cervical Vertebra and Association With Vertebral Canal Stenosis and Articular Process Osteoarthritis in the Horse

Abstract: The sixth cervical vertebra (C6) has unique morphology due to a ventral extension from the transverse process known as the ventral lamina. Little information was found regarding the prevalence and clinical relevance of morphologic variations. Aims of this observational, retrospective study were to characterize C6 morphologic variations in a large sample of horses. Cervical radiographic studies of 100 horses were retrieved. Data recorded were signalment, clinical history, morphology of the C6 ventral lamina, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
80
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(93 citation statements)
references
References 12 publications
12
80
0
1
Order By: Relevance
“…A radiographic study found these morphologic variations in 13.3% of a random study population and in 15% (21/138) in a group of Warmblood horses with a higher prevalence in mares. Another cross‐sectional radiographic study described a frequency of 33.5% (19/55) in Warmblood horses without sex association , which is again close to our observations. It is possible that geographic, demographic and breed‐related differences can explain the minor differences in frequencies between studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A radiographic study found these morphologic variations in 13.3% of a random study population and in 15% (21/138) in a group of Warmblood horses with a higher prevalence in mares. Another cross‐sectional radiographic study described a frequency of 33.5% (19/55) in Warmblood horses without sex association , which is again close to our observations. It is possible that geographic, demographic and breed‐related differences can explain the minor differences in frequencies between studies.…”
Section: Discussionsupporting
confidence: 91%
“…The retrospective aspect of this study and therefore lack of a standardised diagnostic work‐up might also have influenced the outcome. No radiographic association for presence of other vertebral pathologies such as arthrosis was found in cases nor controls, confirming a lack of association as previously reported . The multivariable analysis was performed in a subset of horses to equalise groups as it was noted that the case group contained some older horses while the control group contained small numbers of different Warmblood breeds.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although robust epidemiological data are lacking, it has been reported that approximately 50% of horses exhibit degenerative changes of the facet joint at spinal level C6/C7 . Supporting this estimation, in a recent study of 100 skeletally mature horses, radiographic changes consistent with osteoarthritis were found in 38 and 50% of horses at spinal levels C5/C6 and C6/C7 respectively .…”
Section: Introductionmentioning
confidence: 99%